Spot goes to the beach - Hill, Eric (London : Puffin Books, 2019)
A fantastic first experiences story - perfect for reassuring little ones who are trying new things. Spot is having fun at the beach, trying out surfing - and learning it's not as easy as it looks! Join Spot for seaside, sunshine and surfing in this fun board book adventure, ideal for celebrating summer.
Keywords: Board - book; Children - stories